The Qur’ānic Covenants: A New Legal Perspective - Soofi, Ahmer Bilal (Islamic Studies, 2024)
This paper explores the Qur’ānic concept of covenants through a legal lens, presenting a structured framework to examine the Qur’ān’s assurances, directives, and obligations as legally cognizable agreements. By integrating theological scholarship with principles of modern contract law, the study identifies Qur’ānic covenants as foundational to divine-human interaction. Through detailed analysis, the paper categorizes these covenants into overarching universal commitments, legal relationships with nonbelievers, and a comprehensive array of believer-specific agreements, including personal, social, and worldly obligations. Emphasizing the Qur’ān’s unique legal architecture, the research illustrates how covenants resemble modern contractual elements such as offer, acceptance, and consideration while maintaining the Qur’ān’s spiritual and transcendental essence. The findings highlight the Qur’ān’s capacity to regulate moral and ethical conduct internally, independent of external legal systems, underscoring its relevance to contemporary faith-based and secular frameworks. This interdisciplinary approach offers profound insights into the Qur’ānic message, reaffirming its role as a self-sustaining system of accountability and ethical universality.